The interrelation between breakfast intake with academic performance, cognitive skills and body mass index BMI among students UiTM Terengganu Branch, Malaysia - Abdul Karim, Noraida; Abdullah, Nur Amalin Hayati; Mahamed Ali, Faliza; Mohd Fuza, Zatul Ifftah; Ismail, Nurul Ashikin (Human Resource Management Academic Research Society, 2021)
Breakfast is the most important meal of the day as nutrient intake is crucial to energize the body and maintain a high metabolic rate at the beginning of the day. Although many breakfasts awareness programs and studies have shown the effects of skipping breakfast, most higher institution students tend to skip breakfast supposedly to decrease their body mass index (BMI). Studies have also debated that skipping breakfast affects students’ academic performance due to low nutrient intake. Therefore, the study investigates the interrelation between breakfast intake and students’ academic performance in Universiti Teknologi MARA (UiTM), Terengganu Branch, Dungun Campus. The findings revealed that breakfast intake significantly impacted the students’ academic performance and cognitive skills. Interestingly, the study discovered that although breakfast intake energizes the body, there is no relationship between the students’ breakfast intake and BMI. Hence, the study provides insight to enhance the understanding of the interrelation between breakfast intake and student performance.